Responses of arbuscular mycorrhizal fungi to multiple coinciding global change drivers. (August 2019) - Weber, Sören Eliot; Diez, Jeffrey M.; Andrews, Lela V.; Goulden, Michael L.; Aronson, Emma L.; Allen, Michael F.
Abstract: A significant challenge for understanding how fungal communities may change in the Anthropocene are the multiple aspects of simultaneous environmental change. To address this challenge, we used a seven-year multi-factorial field experiment in southern California to examine how root-associated fungi respond to aridity, nitrogen deposition, and plant invasions. We hypothesized that all three global change drivers reduce the abundance of arbuscular mycorrhizal fungi responsible for nutrient uptake (edaphophilic AMF), while increasing the abundance of AMF that colonize roots at high rates (rhizophilic AMF). We found that invasive grasses hosted lower abundances of edaphophilic AMF, and higher abundances of rhizophilic AMF and opportunistically parasitic fungi. Aridity reduced overall AMF abundance while N addition altered the allocation of AMF biomass, increasing root colonization while reducing the density of extraradical hyphae. Overall, these results imply that ongoing global change will alter both the composition of AMF and how these fungi interact with plants.